Dilema Bahasa Ragam Formal: Studi Kasus Resistensi dan Kendala Bahasa Lisan Siswa Kelas IX di MtS Pancasila Kota Bengkulu dalam Kegiatan Diskusi dan Presentasi Ilmiah - Rahmawati, Meli; Salamah; Putri Juni Astuti, Dina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to investigate the dilemma of formal register utilization, resistance factors, and oral language obstacles encountered by ninth-grade students of MtS Pancasila Bengkulu City within the framework of discussion and academic presentation activities. A qualitative descriptive method with a case study approach was implemented. Data were collected via participatory observation during classroom discourse, in-depth structured interviews with ten key student informants and Indonesian language instructors, as well as audio-visual documentations of presentation sessions. The data analysis followed the interactive model of Miles, Huberman, and Saldaña, encompassing data condensation, data display, and conclusion drawing. The findings revealed substantial psychological and sociocultural resistance toward utilizing standardized linguistic forms. Students exhibited awkwardness, fear of being perceived as pretentious, and apprehension of peer mockery when using formal language. Dominant linguistic constraints included interference from the native language (Bengkulu Malay), restricted scientific vocabulary, inability to spontaneously construct effective sentences, and articulation errors driven by speech anxiety. The implications of this research stress the necessity for a reorientation in speaking pedagogy by fostering an inclusive, supportive classroom ecosystem, alongside progressive habituation so that formal register is viewed not as a cultural burden but as an essential academic competency.